2017
DOI: 10.3390/ijms18020458
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Determinant-Focused Acinetobacter baumannii Vaccine Designed Using Reverse Vaccinology

Abstract: As one of the most influential and troublesome human pathogens, Acinetobacter baumannii (A. baumannii) has emerged with many multidrug-resistant strains. After collecting 33 complete A. baumannii genomes and 84 representative antibiotic resistance determinants, we used the Vaxign reverse vaccinology approach to predict classical type vaccine candidates against A. baumannii infections and new type vaccine candidates against antibiotic resistance. Our genome analysis identified 35 outer membrane or extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 89 publications
(139 reference statements)
0
42
0
Order By: Relevance
“…Maximum penetration of the bacterial cell wall by NS has been observed due to opposite charges of attraction. These unique properties of multimode of actions and maximum invasion are quite helpful in developing NS as broad-spectrum antibiotics in the future ( Maqbool et al, 2017 ; Ni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum penetration of the bacterial cell wall by NS has been observed due to opposite charges of attraction. These unique properties of multimode of actions and maximum invasion are quite helpful in developing NS as broad-spectrum antibiotics in the future ( Maqbool et al, 2017 ; Ni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…WP_000413999, a siderophore receptor from cluster I, is strongly expressed in the early stages of bacteremia [26]. Moreover, Ni and collogues [48] reported this protein as a vaccine candidate using reverse vaccinology. In this study, we made an attempt to determine the physicochemical characteristics, 3D structure, and immunogenic properties of WP_000413999 followed by their evaluation in the experimental animal model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study has identified 35 outer membrane or extracellular adhesins, as promising A. baumannii vaccine targets. [34]. Among proteins of interest from A. baumannii, AbOmpA has recently been shown to be involved in serum resistance.…”
Section: Discussionmentioning
confidence: 99%